Controle biológico de fungos fitopatogênicos por Phyllosticta citricarpa e sua aplicação para biorremediação de solos contaminados por herbicidas - Gadanhoto, Biana Pelissari (2022)
Citriculture is one of the most representative sectors of the Brazilian agro-industrial scenario. In view of the diseases that most affect this crop, the Citrus Black Spot (MPC) stands out, whose pathogen is the fungus Phyllosticta citricarpa. Essentially an exhibition of capacity in the bark, teasing demand from table trade. In more severe cases the drop in production, in large volume productions. Controlling this pest requires recurrent applications of fungicides, in addition to other pesticides such as herbicides, to control weeds. Many of these environmental chemicals bring adversity and quality of biodiversity. In this scenario, biological control and bioprospecting of natural processes have stood out. The present project explores the bioactive potential of Phyllosticta citricarpa for biological control and soil bioremediation. For this is an antifungal activity of Phyllosticta citricarpa against the phytopathogenic fungi Sclerotinia sclerotiorum, Rhizoctonia solani, Fusarium verticillioides, by means of culture and disc diffusion with crude extractor, where it was possible to determine that an agent of metabolite production is a factor of gross growth of or of cellular resistance structures as in the case of Sclerotinia scleotiorum. Presentation tests with commercial seed treatment similar to chemical fungicides for Soybean, Wheat, Sorghum and Bean crops. For corn, the fungic control was of superior quality to the commercial one. The biodegradation process of contaminated samples with the herbicides used in citrus cultivation, Oxyfluorfem (pre-emergent) and Flumioxazina (pre- and post-emergent) were selected as the method of analysis of respirometry and colorimetry, where it was observed that the biodegradation of contaminants by the action of soil microorganisms and by the presence of Phyllosticta citricarpa generated a greater production of CO2 and consequent biodegradation biodegradation, mainly in the test of the herbicide Oxyfluorfem (852.28 mg of CO2), correlated to the growth velocity test , also showed a better development, even though the morphological characteristics of the fungus had gone through a dysmorphic process. The discoloration tests reaffirm the biodegradation results of the respirometry, where there is the process by the soil microbial community (12 and 15 hours), but present higher biodegradation values added to the study inoculum (7 and 8 hours). The test organisms present sub-lethal effects exposed to the contaminants and when subjected to the presence of the crude extract the toxicity effect is attenuated, reinforcing the effectiveness of the extract in minimizing the negative effects of herbicides in the face of environmental scenarios.